Проблеми забезпечення гідного рівня життя населення регіонів України - Борисенко, Т.М. (Управління економікою: теорія та практика, 2013)
Обґрунтовано визначення гідного рівня життя. Досліджено умови рівня життя населення України та зроблено висновок, що вони не забезпечують параметри гідного життя. Обосновано определение достойного уровня жизни. Исследуются условия уровня жизни населения Украины и делается вывод о том, что они не обеспечивают параметры достойной жизни. At the present stage the term “worthy standard of living” is becoming increasingly common, it came from the international regulations. The European Social Charter sets out the right of workers to have a remuneration that ensures a decent standard of living to them and their families. The worthy standard of living right is consolidated in the constitutions of many countries, including Russia, Belarus. According to the Constitution of Ukraine, the creation of conditions which provide a worthy standard of living is defined as a state policy. Undoubtely, the determination of the standard of living of Ukraine’s population and its differentiation by regions is important. This gives an opportunity to highlight the real picture of the socioeconomic state of the Ukrainian society in the regional context, which is the basis for further improvement of the social policy. To analyse the conditions for achieving a decent standard of living in the regions of Ukraine, the author used statistics of incomes, consumption and property security. Ratio of average per capita money income and the minimum subsistence wage characterizes the real economic possibilities of achieving a certain standard of living of the population in each region, because the cost of the subsistence wage is constantly being reviewed according to the dynamics of the cost of living. The analysis shows that Ukraine has not created the necessary conditions for ensuring decent living standards. The low level of incomes does not provide even a sufficient nutrition. The author came to the conclusion that the regional social policies should be aimed at ensuring effective employment; increasing labor costs; incomes growth;improving the availability of high-quality consumer goods, especially food. It is important to provide the intensification and increase the regional economic and business activity as an economic basis for achieving a worthy standard of living.